Black Muslim perceptions of police respectfulness and stop legitimacy - Khan, Arsala (Journal of ethnicity in criminal justice, 2022)
There is limited understanding of how perceptions of racially discriminatory policing are complicated by ethnicity, particularly among Black Muslims. Given the dual-pronged discrimination they likely experience, this study examines how racial and Muslim identity, systemic racism, and knowledge of Black history influence perceptions of police respectfulness and stop legitimacy among a nationwide sample of Black Muslims. Results determined a negative relationship between perceptions of racism as a major problem in America and police respectfulness and a positive relationship between knowledge of Black history and illegitimate stops. These findings support the continued implementation of policies to eliminate racism and develop a broader understanding of American Black history, as well as speak to the benefits of ongoing police reforms in this regard.